Gekko (Gekko) shiva, a new limestone-dwelling gecko from Sa Kaeo Province, eastern Thailand (Squamata, Gekkonidae) - Pauwels, Olivier S. G.; Meesook, Worawitoo; Donbundit, Nattasuda; Jindamad, Tanasak; Topai, Nittaya; Sumontha, Montri (Zootaxa, 2025)
We describe Gekko shiva sp. nov. from limestone cave and hills in Khlong Hat District, Sa Kaeo Province, eastern Thailand, near the border with Cambodia. The new species, a member of the subgenus Gekko, differs from all currently recognized Gekko species by the following combination of morphological characters and pattern: maximal known snout-vent length of 131.9 mm, lack of contact between nostrils and rostral, 28 or 29 interorbital scales between supraciliaries, 80–86 scale rows around midbody, 18 dorsal tubercle rows at midbody, 35–37 ventral scale rows at midbody, 9–12 precloacal pores in males, one or two postcloacal tubercles on each side of the base of the tail, 13–15 subdigital lamellae on 1st toe and 18 or 19 on 4th toe, no Y-shaped mark on head, white spots on head, brown dorsal background with irregular bands of white spots on dorsum, yellow venter, and greenish golden iris.